Common Book Selection: Game of Thrones Edition - Coleman, Tara L.; Vaughan, Mariya (My University, 2018)
Selecting a common book can feel like a battle for the Iron Throne. To ensure that our book isn't chosen by the faction with the biggest dragon (power) or biggest cache of gold (resources), we employ various strategies to ensure the rightful heir is crowned the ruler of Westeros (K-State). This session provides an insight into the committee selection, data collection processes, and qualitative coding used to determine the final book. We'll share specific strategies that have helped us keep our selection process equitable while validating our claim to the throne and avoiding tyrant kings.
Citation: Coleman, T. and Vaughan, M. (201). Common Book Selection: Game of Thrones Edition. 37th Annual Conference on the First-Year Experience, San Antonio, TX.
Keywords: Common reading program; First-year students; K-State Book Network (KSBN); Engagement